2019
DOI: 10.1364/boe.10.005093
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent fluorescence and volumetric optoacoustic tomography of nanoagent perfusion and bio-distribution in solid tumors

Abstract: Intravenously administered liposomes and other nano-sized particles are known to passively accumulate in solid tumors via the enhanced permeability and retention (EPR) effect, which is extensively explored toward the improvement of diagnosis and drug delivery in oncology. Agent extravasation into tumors is often hampered by the mononuclear phagocytic and renal systems, which sequester and/or eliminate most of the nanoparticles from the body. Dynamic imaging of the tumor microcirculation and bolus perfusion can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…To our knowledge there is no current study investigating (trans)-dermal drug delivery by optoacoustic imaging. However, especially from cancer-related research, several examples showed the use of optoacoustic imaging for the detection of fluorescently labelled drugs or drug carriers, like Cy7 conjugated iron oxide nanoparticles (Cy7-SPION) or PEGylated indocyanine green (ICG) liposomes, within experimental tumors such as breast cancer [ 194 , 195 , 196 ]. Interestingly, recent developments suggest the applicability of optoacoustic induced power waves to transiently open the SC and thus to facilitate drug permeation.…”
Section: And How Can We Measure Them?mentioning
confidence: 99%
“…To our knowledge there is no current study investigating (trans)-dermal drug delivery by optoacoustic imaging. However, especially from cancer-related research, several examples showed the use of optoacoustic imaging for the detection of fluorescently labelled drugs or drug carriers, like Cy7 conjugated iron oxide nanoparticles (Cy7-SPION) or PEGylated indocyanine green (ICG) liposomes, within experimental tumors such as breast cancer [ 194 , 195 , 196 ]. Interestingly, recent developments suggest the applicability of optoacoustic induced power waves to transiently open the SC and thus to facilitate drug permeation.…”
Section: And How Can We Measure Them?mentioning
confidence: 99%
“…Several important aspects and limitations need to be considered when designing an optimal MSIOAM system. Volumetric OA imaging with spherical arrays is known to benefit from their large angular coverage to enable accurate tomographic OA reconstructions 33,34 . Furthermore, in a spherical array geometry, all the individual elements are directed towards the centre of the FOV, thus facilitating higher sensitivity and better OA image quality compared with standard (e.g., linear or planar) array transducers.…”
Section: Discussionmentioning
confidence: 99%
“…To use a linearregression unmixing method, the spectra of interest must be predefined, usually as oxyhemoglobin, deoxyhemoglobin, and another agent of interest. Although linear unmixing models are most commonly used, these models assume that wavelength-and depth-dependent fluence issues are uniform and therefore can be neglected (28). Many different unmixing algorithms have been successfully developed to obtain information of interest, but there is no reference standard.…”
Section: Maccuaig Et Almentioning
confidence: 99%